Pendampingan Pengembangan Produk Pangan Herbal melalui Lomba Cipta Kreasi oleh Desa Tajug, Ponorogo: Product Development Through Herbal Food Creation Competition in Tajug Village, Ponorogo - Rahmawan, Arief; Ma’rifat, Tian Nur; Muhammad, Muhammad; Pratama, Gusti Randy (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Tajug Village is one of the districts affected by Coronavirus Disease (Covid-19) in Siman District, Ponorogo Regency. Generally, people of Tajug’s livelihood is cultivating crops, raising livestock, selling tempe as well as other traditional food, and running a small herbal drink business. Additionally, several sellers promote their products door to door or make to order. Due to the Covid-19 pandemic, those small enterprises decrease in turnover significantly. This is mainly because the number of social events is mostly banned or limited. Meanwhile, the empowerment of family welfare groups in Tajug village has been established in order to shelter community business activities, particularly for housewives. One of their products is herbs drink and unfortunately, their revenue had plunged into 40%. Additionally, they have no adequate knowledge of food safety in terms of how they pick hygiene bottles for their products. The objective of this community empowerment is herbs drink and traditional food business players as well as the members of PKK Tajug. The aim of this program is to encourage featured products in Tajug Village.